2010
DOI: 10.1016/j.bpj.2010.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Regional Variations in Stress Fiber Mechanics in Living Cells with Laser Nanosurgery

Abstract: The ability of a cell to distribute contractile stresses across the extracellular matrix in a spatially heterogeneous fashion underlies many cellular behaviors, including motility and tissue assembly. Here we investigate the biophysical basis of this phenomenon by using femtosecond laser nanosurgery to measure the viscoelastic recoil and cell-shape contributions of contractile stress fibers (SFs) located in specific compartments of living cells. Upon photodisruption and recoil, myosin light chain kinase-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
102
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 36 publications
13
102
0
Order By: Relevance
“…By contrast, peripherally located SFs such as the ones severed in our experiments are primarily regulated by myosin light chain kinase and are thus expected to be minimally perturbed by ROCK manipulation (17,18). To suppress ROCK activity and dissipate central connections, we treated cells with 5 μM Y-27632.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…By contrast, peripherally located SFs such as the ones severed in our experiments are primarily regulated by myosin light chain kinase and are thus expected to be minimally perturbed by ROCK manipulation (17,18). To suppress ROCK activity and dissipate central connections, we treated cells with 5 μM Y-27632.…”
Section: Resultsmentioning
confidence: 96%
“…We then applied SLA on SFs along the FN-free edge and observed their retraction kinetics. As in our previous studies, we fit each retraction curve to a Kelvin-Voigt viscoelastic cable model described by a time constant (τ), which reflects the SF's effective viscosity/ elasticity ratio, and a plateau retraction distance (L o ), which correlates to the elastic energy dissipated by half of the severed SF (3,17,18) (Fig. 1D) (see SI Text and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A and B), suggesting the dynamics of actin turnover and/or assembly are perturbed. To test this, we performed fluorescence recovery after photobleaching (FRAP) experiments using an F-actin live-cell probe (30) and observed a ∼twofold increase in the rate of F-actin fluorescence recovery in sh-14-3-3σ cells (Fig. 2C), consistent with an increase in actin-polymerization kinetics rather than a suppression of filament turnover (31).…”
Section: -3-3σ Correlates With Malignant Progression In Two Models Ofmentioning
confidence: 94%
“…Notably, Kumar et al (34) observed viscoelastic retraction of single actin stress fiber in living cells using nanosurgery and demonstrated that tensional prestress exists in stress fiber bundles. Leveraging the precision of subcellular control of nanosurgery, the spatial tensional variation was mapped by measuring the viscoelastic recoil of contractile stress fibers (38). A similar study has been performed in Caenorhabditis elegans zygotes in which actomyosin meshwork was ablated and the initial outward velocity of adjacent cortex was proportional to cortical tension (39).…”
Section: Optical Ablation Of Intracellular Structuresmentioning
confidence: 99%